Coronary heart disease - Myers, J. Hurley; DxR Development Group (New Jersey : Novartis, 1998)
(Producer) Demonstrates disease development and clinical onset, gives examples of diagnostic procedures for patient evaluation, and offers key management options
System requirements: Macintosh computer; 4 MB available RAM; System 7.0 or higher; 13 in. or larger col. monitor with at least 256 colors
System requirements: IBM-compatible personal computer (386 or better); 4 MB available RAM; Windows 3.1 or Windows 95; Microsoft-compatible mouse; SVGA monitor configured at a minimum resolution of 640 x 480 and 256-col. mode
Keywords: Coronary Disease -- atlases